2018
DOI: 10.2147/ceg.s136429
|View full text |Cite
|
Sign up to set email alerts
|

Refeeding syndrome in the frail elderly population: prevention, diagnosis and management

Abstract: Aging is linked to physiological and pathophysiological changes. In this context, elderly patients often are frail, which strongly correlates with negative health outcomes and disability. Elderly patients are often malnourished, which again is an independent risk factor for both frailty and adverse clinical outcomes. Malnutrition and resulting frailty can be prevented by adequate nutritional interventions. Yet, use of nutritional therapy can also have negative consequences, including a potentially life-threate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
17

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 69 publications
(84 reference statements)
1
34
0
17
Order By: Relevance
“…The risk of developing RFS is suggested to be high especially among malnourished older patients, and is not restricted to enteral or parenteral nutrition. However, due to nonspecific initial symptoms [36] but also due to a lack of knowledge among many physicians [37], the RFS is frequently not diagnosed and consequently not treated in these patients [38]. A recent cross-sectional multicentre-study showed that nearly three-quarters of 342 geriatric hospitalised patients who were at risk of malnutrition demonstrated significant risk of RFS [39].…”
Section: Management Of Malnutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of developing RFS is suggested to be high especially among malnourished older patients, and is not restricted to enteral or parenteral nutrition. However, due to nonspecific initial symptoms [36] but also due to a lack of knowledge among many physicians [37], the RFS is frequently not diagnosed and consequently not treated in these patients [38]. A recent cross-sectional multicentre-study showed that nearly three-quarters of 342 geriatric hospitalised patients who were at risk of malnutrition demonstrated significant risk of RFS [39].…”
Section: Management Of Malnutritionmentioning
confidence: 99%
“…In the ESPEN guideline, it is recommended to pay special attention during the first three days of EN and PN therapy in malnourished individuals to serum levels of phosphate, magnesium potassium and thiamine, which decline in RFS and should be supplemented where appropriate [21]. Accordingly, a recent review [38] also recommends close monitoring of vital parameters, fluid, serum electrolytes and thiamine in older patients at risk of RFS, whereas nutrition repletion should be started slowly and increased cautiously to reach nutritional goals after four to seven days. Using this strategy in a randomised clinical trial, mortality risk was reduced among critically ill patients [40].…”
Section: Management Of Malnutritionmentioning
confidence: 99%
“…As definições de SR na literatura são heterogêneas, mas a maioria depende apenas de distúrbios eletrolíticos, especialmente hipofosfatemia, e outras incluem também sintomas clínicos, sendo considerado um preditor independente de mortalidade (AUBRY et al, 2018).…”
Section: Diagnósticounclassified
“…The refeeding syndrome is a potentially life-threatening metabolic condition occurring in seriously malnourished patients or in patients recovering from severe catabolic diseases (e.g., sepsis, diabetic ketoacidosis) after start of a nutritional therapy. From a pathophysiological point of view, refeeding syndrome is an exaggerated response of the malnourished catabolic body to a nutritional therapy, indeed to anabolism [28,29]. Refeeding syndrome is characterized by severe electrolyte shifts (mainly hypophosphatemia, hypomagnesemia, and hypokalemia), vitamin deficiency (mainly thiamine), fluid overload and salt retention leading to organ dysfunction including cardiac arrhythmias up to death.…”
Section: Complications Of Parenteral Nutritionmentioning
confidence: 99%
“…The refeeding syndrome is most likely to appear within the first 72 h after initiation of the nutritional therapy. A risk stratification of patients before prior to start a nutritional intervention is recommended and can then by adapted according to the risk category [28,29]. Full energy requirements are targeted within five to ten days after initiation of the nutritional therapy depending on the risk category, starting at a low energy rate (5–15 kcal/kg/day) and increasing stepwise.…”
Section: Complications Of Parenteral Nutritionmentioning
confidence: 99%